Engineering of blended nanoparticle platform for cellular uptake improvement - Jiraphong Suksiriworapong (2020)
The 1st Pharmaceutical Sciences Asia Conference 2019 Theme : Pharmaceutical Sciences toward Health Innovation in the Disruptive Era. Bangkok Midtown Hotel, Thailand. August 22, 2019, page 35